SCHOLARS’ VIEW ABOUT APPROACHES OF TEACHING LITERATURE IN EFL CLASSROOMS - Djoldasova, G.B.; Alimbetova, M.M. (SCIENCE and SOCIETY, 2023)
Literature plays an important role in the development of English language, especially in improving communication skills, raising cultural awareness, and generating students' motivation. This article deals with various of approaches which can be helpful for teachers in conducting lessons and the ways of integrating literature in EFL classrooms.